An Application of Adobe Illustrator for a Two-dimensional Surface Food Packaging Design: A Pilot Data Visual Design Elements Analysis - Suhaylah, Raja Intan; Bidin, Azman; Peng, Lim Yan (International Review of Management and Marketing, 2018)
Undoubtedly, it has been proven that the attention given to packaging design is continuously supported by prevalent academic research, particularly in the food and beverage industry. However, there are opposing views which are in favour of the notion that packaging design presents more utilitarian benefits rather than hedonic benefits. Specifically, this paper describes findings based on a grounded theory which incorporates a quantitative method to obtain results to purposefully identify the visual design elements and the hedonic responses on a food packaging design. As a matter of fact, visual design elements identified in this paper act as the means of identification in measuring aesthetic values of a food packaging design with hedonic response as the mediating variable. Essentially, by applying the descriptive statistics as the measurement method, this paper primarily explores the extent and quality of the research instrument. Besides, this paper has utilised 2-D graphic technology via the application of Adobe Illustrator to present a set of visual design elements. In addition, the pilot test result of the perceived visual design elements which were ascertained by the targeted respondents would be taken into consideration for further studies with respect to the design and aesthetic values of 2-D graphic. Keywords: Food Packaging, Two Dimensional, Visual Design Elements. JEL Classifications: M3, M37